Модификации вентильных схем непрерывного контроля изоляции сетей низкого напряжения с изолированной нейтралью - Olszowiec, P. (Електротехніка і електромеханіка, 2016)
Представлена работа разных вентильных схем измерения сопротивления изоляции сетей низкого напряжения с изолированной нейтралью. Приведены формулы для вычисления эквивалентного сопротивления изоляции при асимметрии линейных напряжений сети. Предложены способы устранения недостатков этих схем с использованием однофазных выпрямителей. Показаны возможности реализации системы сигнализации о понижении сопротивления изоляции и поиска места замыкания на землю Представлена робота різних вентильних схем вимірювання опору ізоляції мереж низької напруги з ізольованою нейтраллю. Наведено формули для обчислення еквівалентного опору ізоляції при асиметрії лінійної напруги мережі. Запропоновано способи усунення недоліків цих схем з використанням однофазних випрямлячів. Показано можливості реалізації системи сигналізації про зниження опору ізоляції та пошуку місця замикання на землю Purpose. In the paper there are described few systems of insulation resistance continuous measurement using an imposed DC
test signal delivered by diode rectifiers. Drawbacks of this technique are pointed out and ways of these shortcomings removal
are proposed. Methodology. An improved version of measuring
circuit based on a single-phase diode rectifier is presented. Application of logometric measuring devices is suggested. Results.
A new insulation resistance continuous measuring system is
insensitive to network voltages variation and asymmetry. Modified circuit enables also implementation of a simple device for
alarming the monitored network’s insulation deterioration
and/or earth-fault protection. Originality. Formulas describing
performance of diode rectifiers under asymmetrical supply have
not been available so far. Both innovations (i.e. single-phase
diode rectifier and logometric meter) have not been applied
widely for implementation of continuous insulation monitoring
in live AC IT networks. Practical value. Use of both innovations
will allow to eliminate unrequired dependence of measurement
results on variable network voltages as well as their possible
asymmetry. Exploitation of diode rectifier circuits for earth fault
location is also possible.